Electrocautery Devices With Feedback Mode and Teflon-Coated Blades Create Less Surgical Smoke for a Quality Improvement in the Operating Theater. Issue 27 (July 2015) - Kisch, Tobias; Liodaki, Eirini; Kraemer, Robert; Mailaender, Peter; Brandenburger, Matthias; Hellwig, Veronika; Stang, Felix H.; Kellam., James
<x xml:space="preserve">Abstract</x> Abstract Monopolar electrocautery is a fast and elegant cutting option. However, as it creates surgical smoke containing polycyclic aromatic hydrocarbons (PAHs), it may be hazardous to the health of the surgical team. Although new technologies, such as feedback mode (FM) and Teflon-coated blades (TBs), reduce tissue damage, their impact on surgical smoke creation has not yet been elucidated. Therefore, we analyzed the plume at its source. The aim of this study was to evaluate if electrocautery FM and TBs create less surgical smoke. Porcine tissue containing skin was cut in a standardized manner using sharp-edged Teflon-coated blades (SETBs), normal-shaped TBs, or stainless steel blades (SSBs). Experiments were performed using FM and pure-cut mode. Surgical smoke was sucked through filters or adsorption tubes. Subsequently, filters were scanned and analyzed using a spectrophotometer. A high-performance liquid chromatography (HPLC-UV) was performed to detect benzo[a]pyrene (BaP) and phenanthrene as 2 of the most critical PAHs. Temperature changes at the cutting site were measured by an infrared thermometer. In FM, more surgical smoke was created using SSB compared with TBs (P < 0.001). Furthermore, differences between FM and pure-cut mode were found for SSB and TB (P < 0.001), but not for SETB (P = 0.911). Photometric analysis revealed differences in the peak heights of the PAH spectrum. In HLPC-UV, the amount of BaP and phenanthrene detected was lower for TB compared with SSB. Tissue temperature variations increased when SSB was used in FM and pure-cut mode. Furthermore, different modes revealed higher temperature variations with the use of SETB (P = 0.004) and TB (P = 0.005) during cutting, but not SSB (P = 0.789). We found that the use of both TBs and FM was associated with reduced amounts of surgical smoke created during cutting. Thus, the surgical team may benefit from the adoption of such new technologies, which could contribute to the primary prevention of smoke-related diseases.